Analysis of complications and unsatisfactory results of surgical treatment of degenerative lumbar spinal stenosis in the elderly patients - S. V. Ochkal; V. A. Sorokovikov; V. E. Potapov; S. N. Larionov (Acta Biomedica Scientifica, 2022)
Background. The results of treatment of the elderly patients operated for spinal stenosis allow us to suggest that a cascade of degenerative changes in the spinal motion segments causes the formation of an adjacent level syndrome, pseudarthrosis, and in some cases – the instability in the fixing structure.The aim of the study. To determine the prognostic factors for the adjacent level syndrome in patients after decompressive and stabilizing spinal surgeries.Methods. We carried out a retrospective cohort study of the surgical treatment of 129 elderly patients (over 60 years of age) for the period from January 2018 to March 2022, who underwent surgery at the lumbosacral level of spine for degenerative spinal stenosis.Results. The outcomes of surgical treatment of 129 patients and the results of discriminant analysis of morphometric studies of computed tomography data indicate that the most significant indicators for the development of the adjacent level syndrome are the lordosis angle in the segment adjacent to the operated one (the mean value in the analyzed group is 12.87 ± 2.22°; in the control group – 11.92 ± 2.97°); the anterior height of the adjacent intervertebral disc (the mean value in the analyzed group is 12.70 ± 2.44 mm; in the control group – 11.46 ± 3.58 mm) and the difference of anterior and posterior disc heights at the adjacent level (the mean value in the analyzed group is 5.48 ± 2.84 mm; in the control group – 6.27 ± 2.71 mm).Conclusion. When analyzing the treatment outcomes of 129 elderly patients operated for degenerative spinal stenosis using instrumented spinal fusion, we revealed that in 16 patients, the adjacent level syndrome developed with an increase in the lordosis angle at the level adjacent to the operated segment. An increase in the anterior height of the adjacent intervertebral disc and the decrease in the difference of anterior and posterior disc heights at the adjacent level can be considered as unfavorable prognostic factors (p = 0.83).